ANALISIS FINANCIAL STATEMENT FRAUD DALAM PERSPEKTIF TRIANGLE FRAUD PADA PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2010-2014 - Handy Nugroho (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2017)
This researh aims to identify and analyze the factors affecting financial statement fraud trianglepersperktif fraud in the banking companies listed in Indonesia Stock Exchange (BEI). Fraud triangle intheory cerssey, fraud triangle that pressures, opportunities, rationalization.For the sample of bankingcompanies totaled 6 companies, years of observation in this study was 5 years old, total observation inthis study was 30 sample observations.The results of this study explained that the external pressure (free cash flow) effect negative andsignificant effect on the financial statement fraud (FSF), financial targets (Return On Assets) negativeeffect but not significant effect on financial statement fraud (FSF), personal financial need (ownershipstock) effect negative but not significant effect on financial statement fraud (FSF), innefektif monitoring(total commissioners) negative effect and significant effect to financial statement fraud (FSF). financialstability (total assets) negative effect but not significant effect on financial statement fraud (FSF)